4-1BB-mediated expansion affords superior detection of in vivo primed effector memory CD8+ T cells from melanoma sentinel lymph nodes - Sluijter, B J R (Clinical immunology (Orlando, Fla.), 2010)
Copyright © 2010 Elsevier Inc. All rights reserved.